Perbandingan Intensitas Birahi Sapi Potong Setelah Induksi PGF2α Tunggal dan Kombinasi PGF2α–Estradiol pada Fase Luteal - Hasrin Hasrin; Athhar Manabi Diansyah; Hasman Hasman; Sri Helda Wulandari; Anggun Permata Sari; Syamsudin Syamsudin; Asma’ul Fitriana Nurhidayah (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2026)
Lust induction is an activity to standardize the occurrence of estrus and ovulation symptoms in livestock by manipulating the female reproductive organs using hormone preparations. This study aims to accelerate the acceleration of estrus in beef cattle by using hormone induction so that mating can be carried out as soon as possible. This study used 10 non-pregnant beef cattle in the Luteal phase and in healthy condition. The sample was randomized and divided into 2 groups with each group consisting of 5 cows (each group 5 replications). In group P1, the sample was injected with a single prostaglandin (PGF2α) of 2ml/head, and in group P2, the sample was injected with prostaglandin (PGF2α) of 2ml/head + estradiol of 5ml/head. This study will compare the estrus rate and intensity of estrus based on scores 1, 2, and 3. The parameters used in the study were estrus rate and intensity of estrus. The data obtained in the study were tabulated using the Excel program and analyzed statistically using the Chi-Square test. The results showed no difference in estrus rate (P>0.05) between groups P1 and P2, both showing 100% estrus. However, the intensity of estrus/estrus score showed a very significant difference (P<0.05) between groups P1 and P2. Therefore, it can be concluded that the use of prostaglandin hormone (PGF2α) in the P2 group as much as 2 ml/head + estradiol as much as 5 ml/head is more effective in inducing estrus in beef cattle.